RESPON SALINITAS TERHADAP PERTUMBUHAN DAN KOMPOSISI RANTAI PANJANG POLYISOPRENOID SEMAI MANGROVE Avicennia officinalis - Apriliyani Apriliyani; Mohammad Basyuni; Lollie AP Putri (Peronema Forestry Science Journal, 2015)
Effect of salinity on the growth and composition of long chain polyisoprenoid in A. officinalis was studied in the greenhouse, Faculty of Agricultural and forest ecology laboratory, University Sumatera Utara. Research was started from July to December 2014. A. officinalis seedlings were used with five levels of salinity namely 0%; 0.5%; 1.5%; 2% and 3% and  grown for 3 months. The optimum result was mostly obtained at a rate of 0% salinity, height growth of seedling was at 2% salinity, diameter growth of seedlings was in salinity 0%, the number of leaves was at 0% salinity, leaves area was at 0% salinity, wet weight and dry of leaves, roots and stems were at  0% salinity respectively. On the other hand, ratio of shoots to roots was at 0% salinity. One-dimensional plate thin-layer chromatography (1D-TLC) analysis of the three months of A. officinalis could not find the dolichol content.Keywords : Mangrove, Avicennia officinalis, salinity, morphology, polyisoprenoid.